1993
DOI: 10.1152/ajpgi.1993.264.2.g280
|View full text |Cite
|
Sign up to set email alerts
|

Role of nitric oxide in gastric hyperemia induced by central vagal stimulation

Abstract: The effects of N omega-nitro-L-arginine methyl ester (L-NAME), an inhibitor of nitric oxide (NO) synthesis, on the vagal cholinergic increase in gastric mucosal blood flow (GMBF) and acid secretion induced by intracisternal injection of the thyrotropin-releasing hormone (TRH) analogue, RX 77368, were studied. GMBF and acid secretion were measured simultaneously by the hydrogen gas clearance technique and titration of gastric perfusate in urethan-anesthetized rats. RX 77368 (30 ng) injected intracisternally sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0
1

Year Published

1993
1993
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 0 publications
3
25
0
1
Order By: Relevance
“…TRH delivered to DMN neurons or injected intracisternally stimulates the activity of preganglionic vagal motor neurons, gastric vagal efferent fibers, and gastric myenteric neurons (32,34,51). This results in a vagal cholinergicdependent stimulation of gastric acid secretion, motility, emptying, and mucosal blood flow in rats and cats (15,46,49). TRH actions in the brain are mediated by an interaction with two TRH receptors, subtypes 1 (TRH 1 ) and 2 (TRH 2 ) (5, 6).…”
mentioning
confidence: 99%
“…TRH delivered to DMN neurons or injected intracisternally stimulates the activity of preganglionic vagal motor neurons, gastric vagal efferent fibers, and gastric myenteric neurons (32,34,51). This results in a vagal cholinergicdependent stimulation of gastric acid secretion, motility, emptying, and mucosal blood flow in rats and cats (15,46,49). TRH actions in the brain are mediated by an interaction with two TRH receptors, subtypes 1 (TRH 1 ) and 2 (TRH 2 ) (5, 6).…”
mentioning
confidence: 99%
“…The process is likely to be vagal dependent, and biochemical and pharmacological studies have shown that vagal cholinergic pathway stimulates gastric prostaglandin and nitric oxide release. In addition, vagal muscarinic mediated release of prostaglandins, histamine and serotonin [147,150] evoke sensory C-fiber excitation and a subsequent release of neuropeptides from sensory nerve endings.…”
Section: Resultsmentioning
confidence: 99%
“…), which induces ablation of primary sensory neurons and the depletion of CGRP-containing fibers, pharmacological blockade of peripheral CGRP 1 receptors by hCGRP 8-37 and NO synthesis by NO-synthase inhibitor N ω -nitro-L-arginine methyl ester blocked the increased gastric mucosal blood flow induced by i.c. injection of TRH [149][150][151][152][153]. The results indicate that the intact function of sensory fibers containing CGRP and NO is basically important for stimulation of gastric mucosal blood flow and the consequent gastroprotection [152], and the CGRP/NO-mediated gastric hyperemia plays a crucial role to withstand gastric mucosal damage [reviews 61,154].…”
Section: Role Of Capsaicin Sensitive Afferent Fibers and In The Actiomentioning
confidence: 99%
“…The mechanism by which TRH increases GMBF is postulated to involve the release of nitric oxide or prostaglandins through vagal stimulation (5,20,21). If TRH activates the sympathetic nervous system, it would be rational that the increase in GMBF in response to TRH should be potentiated by pretreatment with a-blockers because of the removal of the suppression by the sympathetic nervous system.…”
Section: Discussionmentioning
confidence: 99%